UNDERGROUND LGBT SOCIETY DI SEKITAR KOTA PALANGKA RAYA - Ademi Sandy (Journal SOSIOLOGI, 2020)
Discrimination Towards LGBT (Lesbian, Gay, Bisexual, Transexual) Community is a major issues that occurs in the modern society. Among all the university students in Palangka Raya there’s few of them, living under fear that maybe someday their identity may be exposed, and when that happen they’ll get a horrible social punishment, from their home enviroment, also from common society everywhere they known for their identity as part of LGBT Community. Under fear of being known they managed to create an “Underground” system to interact with fellow LGBT in a social platform app named “Blued” and also through that application they sometimes secretly arrange a sexual thing to do in real life. In this article, author managed to collect some information about the underground LGBT society among university students in all across Palangka Raya and also maybe all of Palangka Raya in common from former Gay person that still studying in one of university in Palangka Raya which now is currently in healing process to live normally as a straight sexual man.